A glass type multistrip-MRPC prototype for the low rate region of the CBM time-of-flight wall - Deppner, Ingo Martin; Herrmann, Norbert (Journal of Instrumentation, 2012)
The Compressed Baryonic Matter spectrometer (CBM) is expected to be operational in the year 2018 at the Facility for Anti-proton and Ion Research (FAIR) in Darmstadt, Germany. The key element providing hadron identiﬁcation at incident energies between 2 and 10 AGeV is a Time-of-Flight (ToF) wall covering the polar angular range from 2.5◦-25◦ and full azimuth. The necessary particle identiﬁcation capabilities require a 80 ps system time resolution at high efﬁciency and, simultaneously, a rate capability of up to 25 kHz/cm2. The existing conceptual design foresees a 120 m2 ToF-wall composed of Multi-gap Resistive Plate Chambers (MRPC) which is subdivided in ﬁve rate depending concentric arranged regions named A to E where A is the area having ﬂuxes below 1 kHz/cm2 in average. For this region A which covers approximately 55% of the total area we developed a Multistrip-MRPC containing ﬂoat glass as resistive electrode material. In this paper we present the design of this prototype and in particular results obtained during in beam tests at GSI/SIS18 at Darmstadt and COSY at Ju¨lich.
Gesehen am 10.12.2018